2006
DOI: 10.1080/00288233.2006.9513732
|View full text |Cite
|
Sign up to set email alerts
|

Threshold model analysis of lamb survivability in Romney sheep

Abstract: of 80.8%. Lambs were born between 1997 and2000. Fixed effects fitted in the model included sex and contemporary group, defined as the interaction of age of dam, flock, and birth date class. Median heritabilities were 0.106 ± 0.010 for direct, 0.082 ± 0.005 for maternal, and a median proportion of phenotypic variation 0.098 ± 0.003 for permanent environmental effects. The direct-maternal correlation was -0.75 ± 0.03. Estimated breeding values on the underlying scale were back-transformed to the phenotypic proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
4
1
Order By: Relevance
“…Since maternal genetic effects were not fitted, the current results also excluded the direct-maternal genetic correlation (r am ) as a component of variance affecting lamb survival. This is in contradiction to the negative and large r am estimate of -0.60 previously reported by Cloete et al (2009), an estimate that was similar to the r am of -0.75 also derived from threshold analysis by Welsh et al (2006). The issue surrounding r am is pertinent if found to have a biological significance, since it counter-intuitively implies that ewes with a high genetic tendency for survival would tend to be poor mothers.…”
Section: Random Variance Components Of Lamb Survivalcontrasting
confidence: 78%
See 2 more Smart Citations
“…Since maternal genetic effects were not fitted, the current results also excluded the direct-maternal genetic correlation (r am ) as a component of variance affecting lamb survival. This is in contradiction to the negative and large r am estimate of -0.60 previously reported by Cloete et al (2009), an estimate that was similar to the r am of -0.75 also derived from threshold analysis by Welsh et al (2006). The issue surrounding r am is pertinent if found to have a biological significance, since it counter-intuitively implies that ewes with a high genetic tendency for survival would tend to be poor mothers.…”
Section: Random Variance Components Of Lamb Survivalcontrasting
confidence: 78%
“…Similarly, Matos et al (2000) reported that the h 2 of survival from birth to weaning from a threshold model amounted to about three-fold the magnitude of the value derived by linear models in the same study. However, a moderate h 2 estimate of 0.11 for Tsv has also been derived from threshold models (Welsh et al 2006). Compared with the present results, high h 2 estimates of 0.18-0.33 have also been reported for postnatal survivability derived from sire models (Sawalha et al 2007).…”
Section: Random Variance Components Of Lamb Survivalsupporting
confidence: 52%
See 1 more Smart Citation
“…The study of Welsh et al (2006) suggested that examining both individual birth weight and within litter birth weight variation would be a worthwhile approach to improve understanding. Since then a number of studies have examined the impact of these traits on triplet survival.…”
Section: Survivalmentioning
confidence: 99%
“…A large number of factors contribute to lamb survival and therefore unsurprisingly heritability and repeatability estimates for lamb and litter survival are low (Everett-Hincks et al 2005;Safari, Atkins, Fogarty et al 2005Brien et al 2010;Hinch and Brien 2014, Everett-Hincks and Cullen 2009, Ferreira et al 2015Hebart and Brien 2018) indicating slow genetic progress only. Welsh et al (2006) suggested that even slow genetic progress is worth targeting as a long-term solution. Hebart and Brien (2018) indicated that considering lamb survival separately for each birth rank would be more effective than treating it as a single trait across rank.…”
Section: Lamb Survivalmentioning
confidence: 99%